Everything 2.0 : redesign your business through foresight and brand innovation - Manu, Alexander, 1954-; Donaldson, Toni; Shelton, Chris (New Riders, 2008)
"How can individuals and organizations cope with the challenges of our time? By deepening their understanding of human needs and reframing them as what they truly are: desire, wants, and visions of a better self. Provocative author, speaker and leader in the emerging field of strategic foresight, Alexander Manu explains what motivates people and how desire is the driving force to true innovation. Drawing on the principles of the Web 2.0 phenomenon-the empowerment to create, manage and distribute content-this video explores consumers' desire for openness, transparency, and collaboration, and how tapping into this desire can lead to business innovation. Whether you are in the role of strategic product developer, or you are tasked with solving a global problem, this video will leave you with a new frame of reference for positioning your company's future."--Resource description page